Current-mode sinusoidal quadrature oscillator with independent control of oscillation frequency and condition using CDTAs - Tangsrirat, Worapong; Tanjaroen, Wason (My University, 2010)
A current-tunable current-mode sinusoidal quadrature oscillator, constructed from only three current differencing transconductance amplifiers (CDTAs) and two grounded capacitors with the absence of the passive resistors, is presented and analyzed. The proposed oscillator provides the important advantage of non-interactive electronic control of the oscillation condition and the oscillation frequency (ω0) and is capable of generating two quadrature current outputs. The circuit exhibits low active and passive sensitivities and is suitable for integration. Theoretical results are verified with PSPICE simulations.
Keywords: CDTAs; Current-mode sinusoidal quadrature oscillator; Oscillation frequency; Oscillator